Promoting effect of rapamycin on osteogenic differentiation of maxillary sinus membrane stem cells - Yanjun Lin; Min Zhang; Lin Zhou; Xuxi Chen; Jiang Chen; Dong Wu (PeerJ, 2021)
Background Stem cells located in the maxillary sinus membrane can differentiate into osteocytes. Our study aimed to evaluate the effect of rapamycin (RAPA) on the osteogenic differentiation of maxillary sinus membrane stem cells (MSMSCs). Methods Colony-forming unit assay, immunophenotype identification assay, and multi-differentiation assay confirmed characteristics of MSMSCs obtained from SD rats. Transmission electron microscopy (TEM) and flow cytometry (FCM) identified the initial autophagic level of MSMSCs induced by RAPA. Real-time quantitative PCR (qPCR) evaluated subsequent autophagic levels and osteogenic differentiation. Alkaline phosphatase (ALP) activity assay and alizarin red staining (ARS) evaluated subsequent osteogenic differentiation. We performed a histological examination to clarify in vivo osteogenesis with ectopic bone mass from BALB/c nude mice. Results MSMSCs possessed an active proliferation and multi-differentiation capacity, showing a phenotype of mesenchymal stem cells. The autophagic level increased with increasing RAPA (0, 10, 100, 1,000 nM) and decreased over time. ALP activity and calcium nodules forming in four RAPA-treated groups on three-time points (7, 14, 21 d) showed significant differences. Col1a1, Runx2, and Spp1 expressed most in 100 nM RAPA group on 7 and 14 d. Osteogenesis-related genes except for Ibsp expression between four groups tended to be consistent on 21 d. 100 nM and 10 nM RAPA-treated groups showed more bone formation in vivo. Conclusion RAPA can promote osteogenic differentiation of MSMSCs, indicating a possible relationship between osteogenic differentiation and autophagy.